Repetitive transcranial magnetic stimulation alleviates neuropathic pain via microglial polarization by modulating the METTL3/NMDAR2B/NLRP3 pathway - Zhu, Jiayi; Li, Lei; Shi, Rongnan; Xing, Fei; Yang, Yue; Xu, Zhangyu; Wang, Qin; Deng, Qi; Li, Dan; Huang, Maomao; Wang, Jianxiong (Frontiers in Immunology, 2026)
IntroductionNeuropathic pain (NeuP) remains a major clinical condition, and the existing interventions often fail to provide sufficiently satisfactory symptom control. Repetitive transcranial magnetic stimulation (rTMS) has gained attention as a potential non-invasive therapy for NeuP. However, the precise mechanisms underlying the effects of rTMS remain elusive.ObjectiveThis study explores the potential neurophysiological mechanisms of rTMS in NeuP, focusing on its modulation of the methyltransferase-like 3 (METTL3)/N-methyl-d-aspartate receptor subtype 2B (NMDAR2B)/NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3) axis and microglial polarization.MethodsCCI rats began to receive rTMS treatment once daily 7 days after the operation, and the treatment continued for 4 weeks. Pain and depression-like behaviors were evaluated by measuring the paw-withdrawal mechanical threshold (PWMT), thermal pain-induced paw-withdrawal latency (PWL), sciatic nerve function index (SFI), forced swimming test (FST) results, and new object preference index (NPI). The expression levels of relevant indicators were detected by immunofluorescence and western blot analyses, quantitative reverse transcription-polymerase chain reaction (qRT-PCR), and enzyme-linked immunosorbent assay (ELISA). BV2 microglia were cultured in Dulbecco’s modified Eagle medium. After adding agonists and inhibitors of METTL3 and NMDAR2B, the microglia were treated with lipopolysaccharide (LPS; 100 µg/mL) for 12 h. The cells are divided into seven groups: Control (Con), LPS, LPS + magnetic stimulation (MS), LPS + METTL3 inhibition (sh-METTL3), LPS + METTL3 overexpression + magnetic stimulation (LPS+METTL3-OE+MS), LPS + NMDAR2B inhibition (sh-NMDAR2B), and LPS + NMDAR2B overexpression + magnetic stimulation (LPS+NMDAR2B-OE+MS). The expression levels of cell polarization markers, inflammatory factors, and related proteins were detected by methods such as immunofluorescence and western blot analyses, qRT-PCR, and ELISA.ResultsrTMS improved pain thresholds (PWMT, PWL, and SFI) and depressive-like behaviors, reduced immobility in the FST, and increased the NPI. It inhibited the levels of the pro-inflammatory markers interleukin (IL)-6, tumor necrosis factor (TNF)-α, NLRP3,TMEM119 and iNOS in the dorsolateral prefrontal cortex (DLPFC), while increasing the expression of IL-10 and Arg1. Moreover, rTMS decreased the expression levels of the M1-type marker CD86 of microglia and increased those of the M2-type marker CD206 and simultaneously decreased the expression of microglia activation marker Iba-1. rTMS simultaneously downregulated METTL3, N6-methyladenosine (m6A), NMDAR2B, and YTH domain-containing family 1 (YTHDF1). In the in vitro experiments, LPS-induced BV2 cells showed increased expression of CD86 increased (p < 0.01) as well as NLRP3, IL-6, TNF-α, and METTL3/m6A/YTHDF1/NMDAR2B (p < 0.01), and decreased expression of CD206 and IL-10. Magnetic stimulation reversed these effects, promoted the reduction of microglial marker Iba-1, increased M2 polarization and alleviated inflammation (p < 0.01). Inhibition of METTL3 or NMDAR2B alleviated LPS-induced inflammation. However, activation of METTL3 or NMDAR2B counteracted the effects of magnetic stimulation in improving inflammation (p < 0.01). In addition, suppressing or overexpressing METTL3, YTHDF1, and NMDAR2B correspondingly decreased or increased these effects, but modulation of NMDAR2B did not change the expression of METTL3/YTHDF1.ConclusionrTMS can affect the polarization state of microglia and neuroinflammation by regulating the METTL3/NMDAR2B/NLRP3 signaling pathway, thereby improving NeuP.